# SOLUTION: I am having difficulty factoring a problem. 49m^2-42m+9 Any help would be appreciated

Algebra ->  Algebra  -> Polynomials-and-rational-expressions -> SOLUTION: I am having difficulty factoring a problem. 49m^2-42m+9 Any help would be appreciated       Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Polynomials, rational expressions and equations Solvers Lessons Answers archive Quiz In Depth

Question 634761: I am having difficulty factoring a problem. 49m^2-42m+9 Any help would be appreciated

You can put this solution on YOUR website!

Looking at the expression , we can see that the first coefficient is , the second coefficient is , and the last term is .

Now multiply the first coefficient by the last term to get .

Now the question is: what two whole numbers multiply to (the previous product) and add to the second coefficient ?

To find these two numbers, we need to list all of the factors of (the previous product).

Factors of :
1,3,7,9,21,49,63,147,441
-1,-3,-7,-9,-21,-49,-63,-147,-441

Note: list the negative of each factor. This will allow us to find all possible combinations.

These factors pair up and multiply to .
1*441 = 441
3*147 = 441
7*63 = 441
9*49 = 441
21*21 = 441
(-1)*(-441) = 441
(-3)*(-147) = 441
(-7)*(-63) = 441
(-9)*(-49) = 441
(-21)*(-21) = 441

Now let's add up each pair of factors to see if one pair adds to the middle coefficient :

First NumberSecond NumberSum
14411+441=442
31473+147=150
7637+63=70
9499+49=58
212121+21=42
-1-441-1+(-441)=-442
-3-147-3+(-147)=-150
-7-63-7+(-63)=-70
-9-49-9+(-49)=-58
-21-21-21+(-21)=-42

From the table, we can see that the two numbers and add to (the middle coefficient).

So the two numbers and both multiply to and add to

Now replace the middle term with . Remember, and add to . So this shows us that .

Replace the second term with .

Group the terms into two pairs.

Factor out the GCF from the first group.

Factor out from the second group. The goal of this step is to make the terms in the second parenthesis equal to the terms in the first parenthesis.

Combine like terms. Or factor out the common term

Condense the terms.

===============================================================

So factors to .

In other words, .

Note: you can check the answer by expanding to get or by graphing the original expression and the answer (the two graphs should be identical).

--------------------------------------------------------------------------------------------------------------
If you need more help, email me at jim_thompson5910@hotmail.com

Also, please consider visiting my website: http://www.freewebs.com/jimthompson5910/home.html and making a donation. Thank you

Jim
--------------------------------------------------------------------------------------------------------------